The flow density of atoms sputtered from a cathode of cylinder magnetron - Panchenko, O.A.; Goncharov, A.A.; Demchishin, A.V.; Kostin, E.G.; Pavlov, S.N.; Stetsenko, B.V. (Вопросы атомной науки и техники, 2005)
The results of calculations of atom flows, sputtered from a cathode of special cylindrical magnetron sputtering system, presented. The atoms flow in cylinder magnetron will be larger with respect to planar magnetron due to the axial symmetry of the system. It is shown that deposition rate weakly depends on the diameter of substrate. The atoms flow through the sidewall is calculated. The estimations of sputtered atoms concentration near cathode surface are done. Представлені результати розрахунків потоку атомів, що розпилюються з катоду магнетрону спеціальної циліндричної форми. Потік атомів в циліндричному магнетроні виявляється більшим, ніж у плоскому магнетроні, через аксіальну симетрію системи. Показано, що швидкість осадження атомів слабо залежить від діаметру підкладки. Розрахований потік атомів крізь торці катоду. Зроблені оцінки концентрації розпилених атомів поблизу поверхні катоду. Представлены результаты расчетов потока атомов, распыляемых с катода магнетрона специальной цилиндрической формы. Поток атомов в цилиндрическом магнетроне оказывается больше, чем в плоском магнетроне, из-за аксиальной симметрии системы. Показано, что скорость осаждения атомов слабо зависит от диаметра подложки. Рассчитан поток атомов через торцы катода. Сделаны оценки концентрации распыленных атомов вблизи поверхности катода.